Voice Recognition Impairment in a Blind Capgras Patient - I. Reid; A. W. Young; D. J. Hellawell (Behavioural Neurology)
We report a case of a blind woman, M.N., who experienced the Capgras delusion. She thought that her pet cat had been replaced by a replica which was “ill-intentioned” towards her. M.N.'s case shows that the basis of the Capgras delusion cannot lie exclusively in damage to the visual system. However, testing of M.N.'s auditory recognition abilities revealed a deficit in the recognition of familiar voices. This impairment is consistent with the view that the Capgras delusion may arise in connection with damage to recognition mechanisms, and parallels findings of face processing impairments in sighted Capgras patients.